(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This study aims at investigating the explanatory notions based upon the subjective mechanism found in the linguistic presentation. Moreover, this study shows how intuition and subjectivity can be a means for explanatory levels ; it is possible that in addition to a variety of linguistic evidence based arguments there are the so-called intuitive and analogy based mechanisms used to make proper judgments on certain linguistic forms. The data for this study is taken from Alayni’s work Almarah’s Morphological explanation (1361-1451). Accordingly, we provide some accounts on the notion "Subjective explanation" which indicates that it is not only that some linguistic evidence is necessary for the linguistic explanation but it is also that some subjective explanatory mechanisms are indispensible. This observation is attributed to the highly intuitive language faculty that native speakers have in order to make proper judgments on some linguistic forms. At the morphological level, we will apply this notion of "Subjective explanation" in order to find out how to account for the language behavior at the morphological level.